2021
DOI: 10.2147/jmdh.s306324
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perceptions of COVID-19 Among Health Care Professionals, Medical Students, and Dental Students in the GCC Region: A Cross-Sectional Correlational Study

Abstract: Purpose The aim of this study was to assess the levels of awareness and knowledge regarding COVID-19 among healthcare professionals and students in Kuwait and the Gulf Cooperation Council (GCC) region. Materials and Methods An online cross-sectional survey using a previously validated questionnaire was used to assess the awareness and knowledge levels of COVID-19 in this study, which was distributed via various online platforms to include as many participants as possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…Also, educating the public about the new COVID-19 VOCs was the responsibility of the Jordanian ministry of health, followed by physicians, pharmacists, and nurses. This was consistent with results from other studies [6,27,[31][32][33]. For example, a recent cross-sectional Jordanian study reported that healthcare professional's primary source of COVID-19 information is the Jordanian ministry of health and that physicians, pharmacists and nurses are responsible for educating the public [31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Also, educating the public about the new COVID-19 VOCs was the responsibility of the Jordanian ministry of health, followed by physicians, pharmacists, and nurses. This was consistent with results from other studies [6,27,[31][32][33]. For example, a recent cross-sectional Jordanian study reported that healthcare professional's primary source of COVID-19 information is the Jordanian ministry of health and that physicians, pharmacists and nurses are responsible for educating the public [31].…”
Section: Discussionsupporting
confidence: 89%
“…According to the Centers for Disease Control and Prevention (CDC), a variant of concern (VOC) is defined as "a variant for which there is evidence of an increase in transmissibility, more severe disease (e.g., increased hospitalizations or deaths), a significant reduction in neutralization by antibodies generated during previous infection or vaccination, reduced effectiveness of treatments or vaccines, or diagnostic detection failures" [5]. As of August 2022, one COVID-19 variant is regarded as a VOC by the WHO and the CDC [6]; i.e. Omicron (B.…”
Section: Introductionmentioning
confidence: 99%
“…As they are frontline workers, healthcare professionals must learn about and be aware of emerging knowledge regarding the COVID-19 pandemic [1]. In this study, they had the necessary knowledge to understand that COVID-19 could affect anyone, including themselves and is not a disease for any particular race.…”
Section: Nyangu M Ramathebanementioning
confidence: 99%
“…The COVID-19 pandemic has been most devastating worldwide, causing medical, social, and economic impacts and posing significant challenges for health care professionals [1] and vulnerable populations such as the poor, girls, and rural communities who are exposed to educational inequalities due to the pandemic [2]. The SARS CoV-2 continues to mutate, further posing threats to the well-being of health care workers on the frontline.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Olum et al suggested that such media, if used properly, could be beneficial in disseminating information on COVID-19 by the stakeholders (Olum et al, 2020). However, the reliance of the general public on such media indicated that healthcare professionals, need to invest a significant proportion of their time and resources to be active on social media to disseminate correct news (Abdulwahab et al, 2021).…”
Section: Quality Of Outpatient Care During Covid-19 Pandemicmentioning
confidence: 99%